NAVIGATING BUSINESS TRANSFORMATION WITH FUTURE-READY MINDSET - Muhammad Azman; Intan Delia Rustandi; Putri Gayatri (School of Business, IPB University (SB-IPB), 2020)
VUCA Era drives the current business ecosystem significantly to be more complex and experience strong turbulence. This ecosystem also brings the business process based on the customer transformation needs (vibrant, unreal, crazy, and astounding). This condition requires a new way of working to face future challenges. However, most business practitioners still use conventional approaches (fixed mindset) rather than agile mindset. The paper aims to navigate business entities to compound with business ecosystem in era 4.0. The methods used to construct the paper are meta-analysis and integrating simplification theory (IST). To navigate its transformation path, the future ready mindsets – curiosity, explorer, empathy, transformative, experimental, and open mindset - will play a crucial part. Sub-concepts for each of the future-ready mindset have already been mapped and matched up with each VUCA characteristic. Keywords: VUCA, business transformation, business ecosystem, future ready mindset